Triage protocols for mass casualty incidents : An overview 30 years after START - Streckbein, S.; Kohlmann, T.; Luxen, J.; Birkholz, Torsten; Prueckner, S. (Unfallchirurg, 2016)
Since the publication of the first mass casualty triage protocol approximately 30 years ago, numerous adaptions and alternatives have been introduced and are currently in use throughout the world. This variety may represent a challenge for the cooperation between emergency medical providers and the interoperability of emergency medical services often required during mass casualty incidents. To enhance cooperation and interoperability a standardization of triage protocols is required.This survey was carried out in order to identify and characterize published triage protocols on national and international levels. Furthermore, evidence for validation of the identified triage algorithms was discussed and recommendations for standardization of triage protocols are given.In a systematic literature search 59 relevant articles were identified and evaluated with respect to the given objectives.A total of 12 triage concepts were identified and characterized which are categorized according to the basic principle.The endpoints of the studies, the chosen observation units and the mode of data collection were discussed with respect to their impact on validation. Furthermore, the impact of the degree and dynamics of system capacity overload, which are pathognomonic for mass casualty incidents, were discussed.There is not sufficient evidence to declare one of the triage protocols superior in all aspects to the others and no triage protocol has been implemented on a comprehensive level in Germany. In order to initialize a national or regional convergence process towards an interoperability of emergency medical services, the model uniform core criteria for mass casualty triage approach has been identified as being appropriate.
EVALuna2:16711